Financial management : principles and applications - Titman, Sheridan; Keown, Arthur J.; Martin, John D. (Harlow, United Kingdom : Pearson Education Limited, 2018)
The "10 Principles of Finance" formerly "Axioms" provide the framework, or "the big picture" of finance, which ties the major concepts of the book together. This text constitutes a strong basis on which to build future studies and, for those students who are non-finance majors, a lasting understanding in the fundamentals of finance.
Previous edition: 2014
Includes indexes.
BBS
Keywords: Business enterprises -- Finance; Corporations -- Finance; Business & finance